Uninterruptible power supply monitoring system with Visual Basic - Sohiful Anuar, Zainol Murad; Mohd Nazrin, Md Isa; Norazeani, Abdul Rahman (Universiti Malaysia Perlis, 2009)
In industrial process today, reliability of equipment is very important. Power supply must be able to cater the need of industrial process. In case of power failure, backup power supply system must be able to support the main process plant. This is to ensure smooth operation and product quality. In order to do this, uninterruptible power supply (UPS) system can be used as to ensure the reliability, stability and consistency of the entire system. These UPS system must be monitored in order to enable them to react accordingly in response to a fault or power failure. In this project, UPS monitoring system using visual basic is designed to provide a safe and constant 12VDC supply in the case of power disruption. The main power supply, 240VAC is converted to 12VDC as output voltage and a battery will be used as part of the backup system. This system will be able to control the source of power which offers power from LIVE line or power from BATTERY line. The main output voltage is 12VDC and the battery level will be monitored using GUI software created using visual basic.